Proteomics Analysis of Brain Tissue in a Rat Model of Ischemic Stroke in the Acute Phase - Zheng, Fei; Zhou, Yan-Tao; Zeng, Yi-Fu; Liu, Tao; Yang, Zhao-Yu; Tang, Tao; Luo, Jie-Kun; Wang, Yang (Frontiers in Molecular Neuroscience, 2020)
Background: Stroke is one of the leading health issues with high morbidity and mortality rates worldwide. Of all strokes, approximately 80% cases are ischemic stroke (IS). However, the underlying mechanisms on the occurrence of acute IS remain poorly understood because of heterogeneous and multifactorial factors. More potential biomarkers are urgent to reveal the deeper pathogenesis of IS. Methods: We identified potential biomarkers in rat brain tissues of IS using an iTRAQ labeling approach coupled with LC-MS/MS. Furthermore, the bioinformatrics analyses including GO, KEGG, DAVID and Cytoscape were used to present proteomic profiles and to explore the disease mechanisms. Additionally, Western Blotting for target proteins was conducted for further verifications. Results: We found that 4578 proteins were identified according to iTRAQ-based proteomics method. Of these proteins, 282 proteins including 73 up-regulated and 209 down-regulated proteins were observed. Further bioinformatics analysis suggested that the candidate proteins were mainly involved in energy liberation, intracellular protein transport and synaptic plasticity regulation during the acute period. The KEGG pathway enrichment analysis indicated that a series of representative pathological pathways including energy metabolite, long-term potentiation and neurodegenerative diseases-related pathways. Moreover, Western Blotting confirmed the associated candidate proteins which refer to oxidative responses and synaptic plasticity. Conclusions: Our findings highlight the identification of candidate protein biomarkers and provide insight into the biological processes involved in acute IS.